Hydroxycarboxylic acid receptor 3 and GPR84 – Two metabolite-sensing G protein-coupled receptors with opposing functions in innate immune cells. (February 2022) - Peters, Anna; Rabe, Philipp; Liebing, Aenne-Dorothea; Krumbholz, Petra; Nordström, Anders; Jäger, Elisabeth; Kraft, Robert; Stäubert, Claudia
Abstract: G protein-coupled receptors (GPCRs) are key regulatory proteins of immune cell function inducing signaling in response to extracellular (pathogenic) stimuli. Although unrelated, hydroxycarboxylic acid receptor 3 (HCA3 ) and GPR84 share signaling via Gαi/o proteins and the agonist 3-hydroxydecanoic acid (3HDec). Both receptors are abundantly expressed in monocytes, macrophages and neutrophils but have opposing functions in these innate immune cells. Detailed insights into the molecular mechanisms and signaling components involved in immune cell regulation by GPR84 and HCA3 are still lacking. Here, we report that GPR84-mediated pro-inflammatory signaling depends on coupling to the hematopoietic cell-specific Gα15 protein in human macrophages, while HCA3 exclusively couples to Gαi protein. We show that activated GPR84 induces Gα15 -dependent ERK activation, increases intracellular Ca 2+ and IP3 levels as well as ROS production. In contrast, HCA3 activation shifts macrophage metabolism to a less glycolytic phenotype, which is associated with anti-inflammatory responses. This is supported by an increased release of anti-inflammatory IL-10 and a decreased secretion of pro-inflammatory IL-1β. In primary human neutrophils, stimulation with HCA3 agonists counteracts the GPR84-induced neutrophil activation. Our analyses reveal that 3HDec acts solely through GPR84 but not HCA3 activation in macrophages. In summary, this study shows that HCA3 mediates hyporesponsiveness in response to metabolites derived from dietary lactic acid bacteria and uncovers that GPR84, which is already targeted in clinical trials, promotes pro-inflammatory signaling via Gα15 protein in macrophages. Graphical Abstract: ga1 Highlights: Pro-inflammatory GPR84 couples to Gα15 in macrophages. Anti-inflammatory action of HCA3 in macrophages and neutrophils. HCA3 activation inhibits production of reactive oxygen species. HCA3 agonists increase anti-inflammatory interleukin 10 secretion. GPR84-induced pro-inflammatory neutrophil activation is inhibited by HCA3 agonists.